Monocyte-Derived Dendritic Cells Impair Early Graft Function following Allogeneic Islet Transplantation. Issue 2 (February 2017) - Chow, Kevin V.; Carrington, Emma M.; Zhan, Yifan; Lew, Andrew M.; Sutherland, Robyn M.
Islet transplantation can cure type 1 diabetes but is limited by lack of donor organs and early graft dysfunction, such that many patients require multiple transplants to achieve insulin independence. Monocyte-derived dendritic cells (moDCs) arise during inflammation and allograft encounters where they can promote various innate and adaptive immune responses. To determine whether moDCs impair early graft function following allogeneic islet transplantation, we transplanted MHC-mismatched BALB/c (H-2d) islets into diabetic C57BL/6-CCR2. DTR recipients (H-2b) treated with either saline (control) or diphtheria toxin (DT) to deplete moDCs. Graft function was assessed by blood glucose (BG) measurement. DT treatment resulted in specific depletion of graft site moDCs posttransplant. Despite equivalent pretransplant BG levels [27.0 ± 1.3 vs. 29.6 ± 1.1 mM, not significant (ns)], DT recipients achieved lower posttransplant BG levels and better rates of normoglycemia than control recipients (11.0 ± 1.9 vs. 19.1 ± 1.4 mM, p = 0.004) at 1 day posttransplant in diabetic recipients. When a suboptimal donor dose of 200 islets was transplanted, DT-induced moDC depletion resulted in normoglycemia in 78% compared to 25% of control recipients ( p = 0.03). As well as amelioration of graft dysfunction in the immediate peritransplant period, prolonged DT administration (15 days posttransplant) resulted in improved graft survival (21 vs. 11 days, p = 0.005). moDCs impair early graft function post-allogeneic islet transplantation. moDC depletion may allow for improved early graft function, permit transplantation with lower islet masses, and enhance graft survival.